2019
DOI: 10.1126/sciadv.aau7198
|View full text |Cite
|
Sign up to set email alerts
|

VPS4 triggers constriction and cleavage of ESCRT-III helical filaments

Abstract: Many cellular processes such as endosomal vesicle budding, virus budding, and cytokinesis require extensive membrane remodeling by the endosomal sorting complex required for transport III (ESCRT-III). ESCRT-III protein family members form spirals with variable diameters in vitro and in vivo inside tubular membrane structures, which need to be constricted to proceed to membrane fission. Here, we show, using high-speed atomic force microscopy and electron microscopy, that the AAA-type adenosine triphosphatase VP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 58 publications
4
92
0
Order By: Relevance
“…This analysis aligns well with the recent experiments byGoliand et al, in which the geometry change between a ring and a spiral ESCRT-III filament, caused by Vps4, is suggested to drive the constriction of the intercellular membrane bridge between two dividing cells(27). Similarly, Maity et al have recently shown that Vps4 causes changes in the helical radius of ESCRT-III helical filaments in vitro, again suggesting that a geometry change of the filament is underlying ESCRT-III-mediated membrane remodelling(37). Finally,Pfitzner et al have recently demonstrated that Vps4 ATP-ase promotes sequential changes in the composition of various ESCRT-III proteins within the filament, which is directly coupled to the filament's ability to remodel the membrane(28).…”
supporting
confidence: 91%
“…This analysis aligns well with the recent experiments byGoliand et al, in which the geometry change between a ring and a spiral ESCRT-III filament, caused by Vps4, is suggested to drive the constriction of the intercellular membrane bridge between two dividing cells(27). Similarly, Maity et al have recently shown that Vps4 causes changes in the helical radius of ESCRT-III helical filaments in vitro, again suggesting that a geometry change of the filament is underlying ESCRT-III-mediated membrane remodelling(37). Finally,Pfitzner et al have recently demonstrated that Vps4 ATP-ase promotes sequential changes in the composition of various ESCRT-III proteins within the filament, which is directly coupled to the filament's ability to remodel the membrane(28).…”
supporting
confidence: 91%
“…The HS-AFM experiments on lipid bilayers were performed using SLBs composed of 60% DOPC, 30% DOPS, and 10% PI(4,5)P2. The SLBs were formed by incubating LUVs on top of freshly cleaved mica, as described in 39 . Briefly, LUVs were thawed at room temperature and diluted to a concentration of 0.2 mg/ml in buffer (25mM Tris, pH 7.4, 50mM NaCl).…”
Section: Surface Preparation For Hs-afmmentioning
confidence: 99%
“…Common to all ESCRT-mediated processes is the strict requirement of VPS4 that not only recycles ESCRT-III 36 , but actively remodels the polymers in vivo 14,37 and in vitro 38,39 . Vps4/VPS4 ESCRT-III remodeling seems to be critical to complete release 14,40,41 .…”
Section: Introductionmentioning
confidence: 99%
“…Activity of ESCRT-III components and VPS4, the AAA-ATPase that promotes fusion and dissociates ESCRT-III (33,38), are known to be required for efficient assembly of HSV-1 (39,40). However, a recent study of HCMV identified that neither VPS4 nor mammalian ESCRT-III components CHMP4B or CHMP6 are required for assembly, and the authors hypothesized that pUL71 may act as a viral ESCRT-III homologue (41).…”
Section: Discussionmentioning
confidence: 99%